The XPF-ERCC1 Complex Is Essential for Genome Stability and Is Involved in the Mechanism of Gene Targeting in Physcomitrella patens - Guyon-Debast, Anouchka; Rossetti, Patricia; Charlot, Florence; Epert, Aline; Neuhaus, Jean-Marc; Schaefer, Didier G.; Nogué, Fabien (Frontiers in Plant Science, 2019)
The XPF-ERCC1 complex, a highly conserved structure-specific endonuclease, functions in multiple DNA repair pathways that are pivotal for maintaining genome stability, including nucleotide excision repair, interstrand crosslink repair and homologous recombination. XPF-ERCC1 incises double-stranded DNA at double-strand/single-strand junctions, making it an ideal enzyme for processing DNA structures that contain partially unwound strands. Here, we have examined the role of the XPF-ERCC1 complex in the model bryophyte Physcomitrella patens which exhibits uniquely high gene targeting frequencies. We undertook targeted knockout of the Physcomitrella ERCC1 and XPF genes. Mutant analysis shows that the endonuclease complex is essential for resistance to UV-B and to the alkylating agent MMS, and contributes to the maintenance of genome integrity but is also involved in gene targeting in this model plant. Using different constructs we determine whether the function of the XPF-ERCC1 endonuclease complex in gene targeting was removal of 3′ non-homologous termini, similar to SSA, or processing of looped-out heteroduplex intermediates. Interestingly, our data suggest a role of the endonuclease in both pathways and have implications for the mechanism of targeted gene replacement in plants and its specificities compared to yeast and mammalian cells.